2013
DOI: 10.1177/0018726713482012
|View full text |Cite
|
Sign up to set email alerts
|

How age similarity preference, uncertainty, and workplace challenges affect conflict

Abstract: In this article, we propose that age similarity preference (ASP) among employees increases workplace difficulties in an age-diverse environment. Individuals use social categorizations such as age groupings to help minimize uncertainty, cope with change, and deal with complexity. When placed in an age-diverse work environment, intergroup comparisons regarding age become more salient. We suggest that when a preference exists among employees to work and interact with those similar in age to themselves in an age-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Consumers’ own-race preferences have been shown in the sports entertainment market (Kahn, 2000), in consumers’ preferences for television broadcasts (Waldfogel et al, 2004), and in customers’ tipping of servers (Parrett, 2011) and taxi drivers (Ayres et al, 2005). According to the concept of homophily , there is a greater level of comfort in dealing with someone of similar social groups (Ibarra, 1992; Standifer et al, 2013) and comfort is considered particularly important to successful customer interactions (Avery et al, 2012). However, while some studies support this view (Klaver et al, 2005; Zegers de Beijl, 2000), other studies did not find significant effects of client contact on evaluations in hiring situations (Derous et al, 2009; Watson et al, 2011).…”
Section: Contextual Cues In Résumé Screeningmentioning
confidence: 99%
“…Consumers’ own-race preferences have been shown in the sports entertainment market (Kahn, 2000), in consumers’ preferences for television broadcasts (Waldfogel et al, 2004), and in customers’ tipping of servers (Parrett, 2011) and taxi drivers (Ayres et al, 2005). According to the concept of homophily , there is a greater level of comfort in dealing with someone of similar social groups (Ibarra, 1992; Standifer et al, 2013) and comfort is considered particularly important to successful customer interactions (Avery et al, 2012). However, while some studies support this view (Klaver et al, 2005; Zegers de Beijl, 2000), other studies did not find significant effects of client contact on evaluations in hiring situations (Derous et al, 2009; Watson et al, 2011).…”
Section: Contextual Cues In Résumé Screeningmentioning
confidence: 99%
“…Ely (1994) reported that in law offices, women communicated more with other women as the numbers of female attorneys increased. Interpersonal attraction based on homophily tends to increase dysfunctional group dynamics across different demographic groupings (Standifer, Lester, Schultz, & Windsor, 2013).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Individuals have a tendency to promote social categorizations in the form of age groupings and other distinguishing characteristics. The purpose of these categorizations are to help them minimize uncertainty, to deal with complexity and to cope with any unwanted change taking place within their workplace (Standifer et al , 2013). In the current study, this categorization resulted in a perceived conflict between the older and younger employees of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…This could be anything, even in an age-diverse work context or where there is the dominance of one gender. Employees classify themselves and others into groups using criteria that are meaningful and salient to them (Standifer et al , 2013). Such a grouping can then become a powerful tool to shape social behavior in the workplace (Demoulin and Teixeira, 2010).…”
Section: Discussionmentioning
confidence: 99%